E-WOM and Techno Human Relation Approach to Improve Destination Image on Visit at TMII - Darwin Raja Unggul Saragih; Rully Arifiansyah (Enrichment : Journal of Management, 2021)
Tourism as a driver of the global economy in its management in the era of the industrial revolution 4.0 must adapt to the shift in visitor behavior that is increasingly interactive, mobile and personal. This study employs quantitative research methods with a path analysis approach. The data used in this study are primary data and secondary data. The method of data collection in this study was the questionnaire method. The population in this study comprises persons who have traveled to TMII and the population who communicate their trip experiences on online social media accounts. The research instrument employed a questionnaire through numerous items with a Likert scale of 1-5. And data processing using PLS help which consists of Validity Test and Reliability Test. Data analysis in this study uses Convergent Validity and Discriminant Validity. Structural Model Testing comprises of R-square analysis with Blindfolding computation. From the results of the study, it can be seen that 1) Product quality has a significant positive direct effect on visiting decisions; 2) Product quality has a significant positive direct effect on visiting decisions; 3) Product quality has a significant negative direct effect on investment opportunities; 4) Tourism image has a significant positive direct effect on visiting decisions; and 5) Tourism Image has a significant positive direct effect on Visiting Decisions.